2011
DOI: 10.1073/pnas.1012215108
|View full text |Cite
|
Sign up to set email alerts
|

Funneling of gibberellin signaling by the GRAS transcription regulator SCARECROW-LIKE 3 in the Arabidopsis root

Abstract: During plant development, because no cell movement takes place, control of the timing and extent of cell division and coordination of the direction and extent of cell expansion are particularly important for growth and development. The plant hormone gibberellins (GAs) play key roles in the control of these developmental processes. However, little is known about the molecular components that integrate the generic GA signaling into a specific cell/tissue to coordinate cell division and cell expansion. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
260
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(278 citation statements)
references
References 32 publications
12
260
0
1
Order By: Relevance
“…3D). This finding is consistent with previous reports showing that SHR is indispensable for MC formation (Paquette and Benfey, 2005;Heo et al, 2011). Since a reduction of SHR is necessary to permit the formation of MC (Koizumi et al, 2012b), we hypothesized that SEU is required to maintain high levels of SHR that prevent MC formation (Koizumi et al, 2012b).…”
Section: Seu Is An Upstream Activator Of Shr Scr and Scl3supporting
confidence: 82%
See 3 more Smart Citations
“…3D). This finding is consistent with previous reports showing that SHR is indispensable for MC formation (Paquette and Benfey, 2005;Heo et al, 2011). Since a reduction of SHR is necessary to permit the formation of MC (Koizumi et al, 2012b), we hypothesized that SEU is required to maintain high levels of SHR that prevent MC formation (Koizumi et al, 2012b).…”
Section: Seu Is An Upstream Activator Of Shr Scr and Scl3supporting
confidence: 82%
“…During the last decade, several interconnected mechanisms have been proposed to be responsible for the MC formation (Paquette and Benfey, 2005;Cui et al, 2007;Heo et al, 2011;Koizumi et al, 2012a;Koizumi et al, 2012b;Koizumi and Gallagher, 2013). Two GRAS family transcription factors, SHORT-ROOT (SHR; Helariutta et al, 2000) and SCARECROW (SCR; Di Laurenzio et al, 1996), have been shown to play crucial roles in shaping these mechanisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, GRAS proteins have been reported to form homodimers and heterodimers with other GRAS family members and this is likely important for their transcriptional regulation function (Itoh et al, 2002;Cui et al, 2007;Heo et al, 2011;Zhang et al, 2011;Gobbato et al, 2012;Murakami et al, 2013;Xue et al, 2015). Here, our structure of Os-SCL7 was determined in a dimer with helices A12, A79, and A69 at the dimer interface.…”
Section: Discussionmentioning
confidence: 99%